3D anatomical models, adobe flash animation and online communities - Paton, C (MEFANET report, 2008)
Learning objects can be created with a variety of tools and techniques. This paper discusses how learning objects can be developed using 3D models of human anatomy and Adobe® Flash®. The final interactive animations are published as learning objects in Flash format so that they can be embedded in web pages and streamed over the internet. Learning objects can be used in Learning Management Systems such as Moodle or Blackboard, but can also be delivered through online communities. Students who use the online communities can then discuss the learning objects they have viewed with other users in the community’s discussion forums and blogs. This social constructivist technique reinforces the learning they have received by sharing their experiences and thoughts with fellow students.
Keywords: programovaná výuka jako téma; využití lékařské informatiky; Education, Medical; anatomické modely; Audiovisual Aids; Models, Anatomic; New Zealand; audiovizuální pomůcky; počítačem řízená výuka; studium lékařství; Nový Zéland; informatika; Programmed Instructions as Topic; Medical Informatics Applications; Informatics; Computer-Assisted Instruction